(untitled) (ACTIVIDAD FÍSICA Y DESARROLLO HUMANO, 2024)
At school age there are changes in physical abilities that can affect the quality of life in childhood and adulthood; the objective of the study is to compare flexibility in children between 10-12 years old living in rural and urban areas of the metropolitan area of Bucaramanga;, a non-experimental-transversal and descriptive methodology was chosen, with the aim of comparing the flexibility of two groups of children; 13 students from the school in the rural area and 13 students from school in the urban area , giving a total of 26 students, it was obtained in the Paley test in the rural area with 100% with a score of 3 on both sides, in the urban zone with 92% in score of 3 on right side and 100% with a score of 3 on left side; the Sit and Reach test in the rural area a score of 62% in average score is observed, as for the school in urban area we found a percentage of 54% in deficient score. It is concluded that, when evaluating the flexibility in the population from 10 to 12 years of age of the rural and urban schools, a better performance in flexibility will be obtained in the population of the rural area compared to the urban area. This is attributed to the environment and physical activities that children perform in the rural area, in contrast to urban area.